Coding for Indonesian elementary school students: parents’ perceptions - Kurniawati, Atin; Hanafi, Muchtar (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2023)
In the digital era, coding skills have become increasingly prevalent and are now taught in schools. This paper aims to illuminate parents' perceptions of coding education for elementary school students in Indonesia. The study focuses on eight parents who enrolled their children in a coding school in Central Java, Indonesia. To gather data, open-ended questionnaires and semi-structured interviews were conducted. The collected data were subsequently analyzed thematically. The study revealed that parents held positive perceptions of coding skills for elementary school students. This positivity stemmed from their awareness of the rapid development of Information and Communication Technology (ICT), the anticipation of the future impact of ICT skills, trust in the institution, and their children's interest in ICT. Furthermore, parents expressed positive perceptions of their children's progress, attributing it to improved coding skills and positive attitudes. They emphasized the importance of mutual collaboration and communication between parents and schools to enhance the learning experience. In addition to offering a coding curriculum, the school provided parents with up-to-date information about ICT through seminars and regular digital content distribution. The collaboration between the school and parents extended to establishing rules regarding the use of mobile phones and PCs to prevent potential harms from excessive device usage. This suggests that the success of coding education for children necessitates effective collaboration between parents and schools.